A Review on the Application of Nanofluids in Enhanced Oil Recovery - Malika, Manjakuppam; Sonawane, Shriram (Current Nanoscience, 2024)
Oil mobility has been a significant issue since the recovery of a heavy crude reservoir. It is determined by two factors: oil rheological properties and penetrability. Nanofluids (NFs) are a distinct class of engineered fluids characterized by the dispersion of nanoparticles ranging in size from 1 to 100 nanometers (nm) into a working fluid. They are divided into groups based on physicochemical characteristics, including nanoparticle morphology, and thermal and rheological properties. The well-known nanofluids composed of metal (e.g., ZrO2) and ceramic (e.g., SiO2) had the best physicochemical performance in terms of oil mobility. This chapter examines the inundation of metal and nonmetal based nanofluids as a new enhanced oil extraction (EOR) method for extracting primary and secondary oil from more than 45% of confined reservoir fluids. Furthermore, new developments in the utilization of these materials on EOR approaches to combat significant interfacial adhesion across sandstone and fluid interfaces are summarized.
Keywords: nanofluids